Sosialisasi Hadis Salat Tahajud Terhadap Ibu-Ibu Muslimat di Ponpes Nurul Alam Durin Barat - Amelia Aisy; Istiqomah; Nurul Millah; Fatichatus Sadiyah (STARLA: Jurnal Pengabdian Masyarakat, 2026)
Tahajud prayer is a recommended act of worship that holds great merit in Islam, particularly in shaping the spiritual character and discipline of Muslim women. However, amidst domestic and social responsibilities, the motivation and deep understanding of the hadiths regarding the merits and proper procedures of tahajud prayer are often neglected by homemakers. Therefore, there is a need for intensive educational outreach and hadith study programs based on authentic sources to strengthen the understanding and practice of this act of worship. The dissemination of hadiths on Tahajjud prayer is an educational program designed to provide the community with a comprehensive understanding of the hadiths regarding the virtues of Tahajjud prayer as an effort to improve the quality of worship and closeness to Allah SWT. This outreach program is presented in the form of da’wah activities and hadith studies delivered to Muslim women at the Nurul Alam Durin Barat Islamic Boarding School, the majority of whom are married women. The program is conducted using interactive lectures and hadith studies, supplemented by discussions and case studies addressing the challenges of practicing tahajjud in daily life. It is hoped that this program will foster a deeper understanding of the importance of the tahajjud prayer and motivate Muslim women to make it a regular part of their worship routine, so that this act of worship—which is sometimes perceived as difficult—can be made easier through proper understanding.